The Influence of Observability on The Adoption of Tissue Culture Banana Seedlings in Tanzania - Tumaini, Steven; Ghahula, Raphael; Macha, Salvio (European Scientific Journal, ESJ, 2024)
In the seedling’s technology, Banana farming is undergoing a profound transformation with the integration of advanced technologies, referred to as tissue culture banana seedlings. The study delves into the empires of seedling technology and innovations adoption within the banana farming sector. We explore the dynamic interactions between Tissue culture innovation, and the farmer’s adoption. The study adopted positivism philosophy, a cross-sectional survey design, and purposive sampling techniques. A sample size of 350 banana farmers in Kilimanjaro was drawn from the population of the study using Yamen formula for sample size determination. Since the outcome variable was dichotomous the binary logistic regression model was employed. The results indicate that, the highest mean was for the statement “Banana tissue culture seedlings grow faster compared to local suckers” (M=3.75), indicating the speed of growth is seen as a clear observable benefit. Standard deviations were relatively low, ranging from 0.826 to 0.872, indicating less variation in responses. These results suggest smallholder farmers perceive tissue culture banana seedlings as having moderately high observability, especially related to the visible benefits of faster planting growth and income generation compared to using local banana seedlings. We shed light on the adoption of tissue culture seedlings. Adoption is reshaping traditional suckers’ practices, enhancing productivity and business opportunity. Farmers adoption will leads to the economic development and job creation. Farmers markets provide opportunities for small farmers and businesses to sell their products, and support to meet the growing demand for locally produced food.